Unveiling the Hidden Power of Employer Branding in PT Menara Terus Makmur's Recruitment - Astuti, Irma Wiji; Dwianto, Agung Surya (Economics and Digital Business Review, 2024)
This research aims to reveal the hidden power of Employer Branding in the recruitment process at PT Menara Terus Makmur. In an effort to understand how Employer Branding influences recruitment at the company, a qualitative approach was used to explore employees' experiences and perceptions related to Employer Branding and the recruitment process at PT Menara Terus Makmur. The research method involved in-depth interviews with various hierarchical levels of employees, direct observation in the work environment, and analysis of internal company documents. The results showed that Employer Branding has a significant role in influencing the recruitment process at PT Menara Terus Makmur. Findings show that employees have a strong perception of the company's image as an attractive place to work, supported by an inclusive organizational culture and emphasized company core values. Effective communication of the company's culture, career opportunities, and employment benefits through various channels, including social media and recruitment events, proved to be an effective strategy in strengthening the company's Employer Branding. The implication of this study is that it is important for companies to actively pay attention to their Employer Branding strategy in a bid to attract and retain quality talent. Effective communication strategies, emphasis on positive organizational culture, and satisfying employee experiences are key in building a strong corporate image as an attractive place to work.